Outras Inquisições: apontamentos sobre sistematizações, Hermenêutica e História Oral - Garnica, Antonio Vicente Marafioti [UNESP] (My University, 2010)
The starting point of this paper are some avaliable analyses and characterizations about the academic production in History of Mathematics Education in Brazil. A specific reading of such readings – an hermeneutical approach of those avaliable reviews – allows us to put the focus on some features of Oral History thought as a qualitative methodological approach to researches in Mathematics Education.

O ponto de partida deste artigo são algumas análises e sistematizações disponíveis sobre a produção brasileira em História da Educação Matemática no Brasil. Uma leitura dessas leituras – uma abordagem hermenêutica, portanto – leva a considerações sobre a História Oral como metodologia qualitativa de pesquisa para a Educação.
Other inquiries: notes on oral history and the history of mathematical education
Keywords: Reviews; Hermeneutics; Oral History; History of Mathematics Education; Sistematizações; Hermenêutica; História oral; História da educação matemática